Pemanfatan Sampah Plastik sebagai Rumah Bakteri dalam Upaya Pengurangan Limbah - Anggini; Halbi Halbi (Macoa : Jurnal Pengabdian kepada Masyarakat, 2026)
Plastics are among the most widely used materials in human life due to their lightweight, strong, and durable properties. However, these advantages have become a serious problem when plastics end up as waste. The fact that plastics are difficult to decompose naturally leads to the accumulation of plastic waste in the environment, both on land and in water. Data show that plastic waste continues to increase every year, causing negative impacts such as soil and water pollution, as well as posing threats to ecosystems. Conventional waste management methods, such as burning or landfilling, have not been fully effective, as they can create new problems such as air pollution and limited landfill space. One of the emerging solutions is the use of biotechnology approaches, specifically by utilizing microorganisms, particularly bacteria, in the plastic degradation process. Bacteria have a natural ability to produce certain enzymes that can break down plastic polymer chains into simpler compounds. However, the effectiveness of bacteria in degrading plastics is often influenced by environmental factors and the availability of suitable growth media. Therefore, innovation is needed to provide a proper container or “home” for bacteria so that they can live, grow, and function more optimally. The utilization of plastic waste itself as a bacterial habitat is an intriguing concept. This approach not only reduces the amount of discarded plastic but also allows bacteria to begin the degradation process directly on the very material causing the problem. Thus, this strategy is expected to contribute to reducing plastic waste while supporting the achievement of sustainable development ensuring that the preservation efforts of Palippis Beach can continue consistently and bring long-term positive impacts for both the tourism sector and coastal ecology.